By-Laws, Rules and Regulations : 2011. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper describes by-laws of the IMF. These by-laws state that special meetings of the Board of Governors may be called at any time by the Board of Governors or the Executive Board and shall be called upon the request of fifteen members of the IMF or of members of the IMF having in the aggregate one-quarter of the total voting power. Whenever any member of the IMF requests the Executive Board to call a special meeting of the Board of Governors, then the member shall state the reasons.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet